Brief Report: Longitudinal Patterns of Response to Standard of Care Therapy for Systemic Lupus Erythematosus: Implications for Clinical Trial Design. Issue 4 (29th March 2017) - Kim, Mimi; Merrill, Joan; Kalunian, Kenneth; Hahn, Bevra; Roach, Anita; Izmirly, Peter
Abstract : Objective: To evaluate longitudinal patterns of response to standard of care for systemic lupus erythematosus (SLE) in clinical trials and to identify characteristics that differentiate nonresponders from persistent responders. Methods: Data on 147 patients with moderately to severely active SLE without acute nephritis who were treated with placebo plus standard of care in two 52‐week phase II/III trials were obtained from the Collective Data Analysis Initiative of the Lupus Foundation of America. Cross‐sectional and longitudinal analyses of British Isles Lupus Assessment Group (BILAG)–based responses (improvement in all baseline A or B scores without new flare) were performed. Baseline characteristics that discriminated persistent responders from nonresponders were identified using logistic regression. Results: Cross‐sectional response rates decreased from 46% to 37% between 12 and 52 weeks. The overall rate of complete and sustained response, i.e., response at all visits, was only 14.3% (95% confidence interval 8.6–19.9%). Agreement between response status at 12 weeks and 36–52 weeks was low (κ = 0.15–0.29), and only 31% of initial 12‐week responders maintained response at all subsequent visits. Baseline factors predictive of persistent response to standard of care included fewer organs with active disease, high C3 levels, and type of background therapy. Conclusion: Use of sustained rather than landmark response may reduce high placebo response rates in SLE trials that continue aggressive standard of care. Further exploration to assess the power of this end point to improve discrimination between active and placebo arms is indicated. Lack of temporal stability in response highlights a potential weakness with shorter studies. Rates of response to standard of care are affected by the severity of the disease and the aggressiveness of background immunosuppressive treatments.